2023
DOI: 10.3390/vaccines11111668
|View full text |Cite
|
Sign up to set email alerts
|

Information Consumption, Trust Dynamics and COVID-19 Vaccine Hesitancy among Older Adults: Implications for Health Messaging

Yiyi Wu,
Mark Brennan-Ing

Abstract: Staying well informed about the evolving COVID-19 pandemic and vaccine recommendations is vital for older adults, especially for low-income older adults, who have been disproportionately impacted by the pandemic. However, the overwhelming infodemic poses a significant challenge, affecting vaccine decision-making. This study explores how a group of predominantly low-income older adults navigate health information and how their trust in information and vaccines evolves throughout the pandemic. Our objective is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, it showed that older adults aged 65-74 years were about two times more likely to be "very hesitant" and "somewhat hesitant". This could be due to a history of previous hesitancy, distrust in government, misinformation, and vaccine brands influencing vaccine intentions during the pandemic [59,[83][84][85]. The results may suggest a worsening case of vaccine hesitancy since one would expect that age group to be more receptive than older adults.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, it showed that older adults aged 65-74 years were about two times more likely to be "very hesitant" and "somewhat hesitant". This could be due to a history of previous hesitancy, distrust in government, misinformation, and vaccine brands influencing vaccine intentions during the pandemic [59,[83][84][85]. The results may suggest a worsening case of vaccine hesitancy since one would expect that age group to be more receptive than older adults.…”
Section: Discussionmentioning
confidence: 89%
“…A multi-stage probability sampling design of United States households involving geographical stratification, clustering, and oversampling of certain demographic groups was used for the HRS study [59,69]. This multi-stage area probability design consists of four stage selections the primary stage selection details information regarding core samples, Hispanic supplements, Black supplements, and Florida oversampling; the secondary stage selection of area details information of second-stage sampling unit (SSU) stratification, selection, and allocation; the third stage focuses on the selection of housing units-located geographical area; and the fourth stage details participant selection, in which the interviewer made a list of all household members within each sampled housing unit [70].…”
Section: Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation